TREASURY SINGLE ACCOUNT (TSA): IMPACT ON LIQUIDITY OF COMMERCIAL BANKS (Journal of Global Accounting, 2023)
The study presents empirical evidence on the impact of Treasury Single Account on liquidity in the Nigeria banking industry using annual financial report data for the period 2010-2016. The research used the ex-post facto research design. The target population comprised of the commercial banks in Nigeria. The study made use of secondary data extracted from annual reports of studied banks. These data were analyzed using descriptive statistics and Paired Samples t test. Contrary to most previous empirical works and past assertions, the implementation of Treasury Single Account policy had no significant effect on current ratio, liquidity coverage ratio, capital adequacy ratio and a significant increase in loan-deposit ratios. It was recommended that banks uphold strategies to invest in other sectors and aggressive marketing to boost liquidity.
Keywords: Treasury Single Account; Liquidity; Banks